CIRC Classification 2016 - Torres-Salinas, Daniel; Repiso, Rafael (Anuario ThinkEPI, 2016)
A few years ago we had, in Spain, various products for evaluating journals that were useful to researchers and to the Spanish accreditation agencies: Aneca and Cneai. Given the number of products, various research groups collaborated to create a single, unified product:Â Clasificación integrada de revistas científicasÂ (CIRC) (Integrated classification of scientific journals) with the aim of using it with current research information systems (CRIS). The CIRC classification gave each journal a score (A, B, C, D) and was last updated in 2012. EC3metrics is now announcing the launch of a new CIRC version updated for the current situation, while trying to rescue the original intention of the first version that emphasized CRIS integration. This article describes some of the improvements and changes that have been made in the newly updated version.